Intrinsic and Regulated Gonadotropin-Releasing Hormone Receptor Gene Transcription in Mammalian Pituitary Gonadotrophs - Janjic, Marija M.; Stojilkovic, Stanko S.; Bjelobaba, Ivana (Frontiers in Endocrinology, 2017)
The hypothalamic decapeptide gonadotropin-releasing hormone (GnRH), acting via its receptors (GnRHRs) expressed in pituitary gonadotrophs, represents a critical molecule in control of reproductive functions in all vertebrate species. GnRH-activated receptors regulate synthesis of gonadotropins in a frequency-dependent manner. The number of GnRHRs on the plasma membrane determines the responsiveness of gonadotrophs to GnRH and varies in relation to age, sex, and physiological status. This is achieved by a complex control that operates at transcriptional, translational, and post-translational levels. This review aims to overview the mechanisms of GnRHR gene (Gnrhr) transcription in mammalian gonadotrophs. In general, Gnrhr exhibits basal and regulated transcription activities. Basal Gnrhr transcription appears to be an intrinsic property of native and immortalized gonadotrophs that secures the presence of a sufficient number GnRHRs to preserve their functionality independently of the status of regulated transcription. On the other hand, regulated transcription modulates GnRHR expression during development, reproductive cycle, and aging. GnRH is crucial for regulated Gnrhr transcription in native gonadotrophs but is ineffective in immortalized gonadotrophs. In rat and mouse, both basal and GnRH-induced Gnrhr transcription rely primarily on the protein kinase C signaling pathway, with subsequent activation of mitogen activated protein kinases. However, continuous GnRH application, after a transient stimulation, shuts off regulated but not basal transcription, suggesting that different branches of this signaling pathway control transcription. Pituitary adenylate cyclase activating polypeptide, but not activins, contributes to the regulated transcription utilizing the protein kinase A signaling pathway, whereas a mechanism by which steroid hormones modulate Gnrhr transcription has not been characterized.